Pyrene-Imidazole Based Aggregation Modifier Leads to Enhancement in Efficiency and Environmental Stability for Ternary Organic Solar Cells - Lin, Hui; Du, Xiaoyang; Li, Lijuan; Zheng, Caijun; Tao, Silu (Frontiers in Chemistry, 2018)
A novel pyrene-imidazole derivative (PyPI), which can form effcient π-π stacking in solid film, has been utilized in organic solar cells (OSCs). The stacking of small molecule PyPI can facilitate charge transfer and suppress fullerene aggregation. As a result, PTB7-Th: PyPI: PC71BM based ternary OSC exhibits a high PCE of 10.36%, which presents 15.88% enhancement than the binary device (8.94%). Concurrently, the ternary OSC shows much better thermal and light illumination stability. Under continuous 60 oC annealing for 3 hours in atmosphere, the device still remains 94.13% efficiency than the pristine state, while the control device only keeps 52.47% PCE. In the condition of constant illuminating under AM 1.5G irradiation (100 mW cm-2) in atmosphere, the PCE of OSC keeps at 72.50%. The high conversion efficiency and excellent environmental stability of PyPI based ternary OSC narrowed the gap between laboratory investigation and industrial production.